A systematic review on the eating behaviors of youth exceeding electronic device recommendations - Coleman, Anna; Neumann, Devin; Cole, Angela Sasaki; Brady, Clark; Park, Alex; Odisho, Jason; Moschke, Kaylynn; Nauts, Logan (Frontiers in Psychology, 2025)
BackgroundAs the rates of both disordered eating and electronic device usage in youth and adolescents have increased over the last two decades, several studies have looked to determine if there is any relationship between the two variables. While excessive screen use has broadly been shown to correlated with abnormal eating behaviors, newer research reveals that different types of screen use (e.g., social media, television, or video games) affect eating behaviors in youth and adolescents. The goal of this systematic review is to analyze to what extent different types of screen use are associated with disordered eating habits, as well as assess for nuance in both the age of the population studied, as well as the geographic location of the study.MethodsA search of relevant terms was conducted from PubMed (n = 1,234) and Scopus (n = 301) in July of 2024. Included articles examined the relationship between one or more types of screen use and eating behaviors or disorders, were published between 2014 and 2024, and involved participants aged 0–17. Exclusion criteria consisted of articles solely looking at BMI and/or diet as an outcome, as well as articles that studied an adult population. Risk of bias was assessed using the MMAT® 2018 criteria.ResultsSixteen studies were included in the final analysis, majorly consisting of cross-sectional studies. Results indicated that while there is overwhelming evidence that excessive screen use is correlated with disordered eating habits at large, individual trends in disordered eating vary depending on the type of screen exposure. Furthermore, some studies suggest that disordered eating is a secondary sequela associated with screen time, with the primary cause being lack of sleep or poor mental health.DiscussionThis review is limited by small number of included studies, high number of cross-sectional studies, and small number of studies looking at populations under age twelve. These findings provide opportunities for both clinicians to evaluate their pediatric patients more holistically when treating for disordered eating behaviors. Furthermore, both clinicians and public health officials alike should consider type of screen time when making recommendations for healthy amounts of screen time for children and adolescents.